1992
DOI: 10.1038/ki.1992.404
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose intravenous calcitriol treatment of secondary hyperparathyroidism in hemodialysis patients

Abstract: Intravenous calcitriol is known to directly suppress PTH secretion and release. We evaluated the effect of four months of treatment with low-dose intravenous calcitriol on PTH levels in 83 hemodialysis patients. The criteria for including patients in the study were a serum PTH levels at least four times the normal limit, a serum total calcium less than 10 mg/dl and good control of the serum phosphorus level. All patients underwent standard bicarbonate or acetate dialysis; dialysate calcium level was maintained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0
3

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(28 citation statements)
references
References 25 publications
1
24
0
3
Order By: Relevance
“…In an observational study that included Ͼ30,000 hemodialysis patients, Teng et al (43) showed a 20% reduction in mortality among patients who were treated with active vitamin D derivatives compared with those who were not treated; subgroup analyses showed a benefit of active (44) recently demonstrated progressive aortic calcification in rats that had SHPT and were treated with calcitriol, whereas vehicle-and cinacalcet-treated rats had no significant calcification, although extremely high doses of calcitriol were used (100 ng, corresponding to 0.25 to 0.28 g/kg body wt). In humans, broad clinical experience has demonstrated increased Ca and P levels with vitamin D therapy (34,(45)(46)(47). In a pooled post hoc analysis of prospective, randomized studies, a significant reduction in hospitalization for cardiovascular disease and fracture and an improvement in self-reported physical function were observed among patients who were randomly assigned to cinacalcet versus placebo when added to conventional therapy (48).…”
Section: Discussionmentioning
confidence: 99%
“…In an observational study that included Ͼ30,000 hemodialysis patients, Teng et al (43) showed a 20% reduction in mortality among patients who were treated with active vitamin D derivatives compared with those who were not treated; subgroup analyses showed a benefit of active (44) recently demonstrated progressive aortic calcification in rats that had SHPT and were treated with calcitriol, whereas vehicle-and cinacalcet-treated rats had no significant calcification, although extremely high doses of calcitriol were used (100 ng, corresponding to 0.25 to 0.28 g/kg body wt). In humans, broad clinical experience has demonstrated increased Ca and P levels with vitamin D therapy (34,(45)(46)(47). In a pooled post hoc analysis of prospective, randomized studies, a significant reduction in hospitalization for cardiovascular disease and fracture and an improvement in self-reported physical function were observed among patients who were randomly assigned to cinacalcet versus placebo when added to conventional therapy (48).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to PTH, serum Ca and P levels are sensitive to vitamin D treatment (9,10,25,26). The increased serum mineral levels can contribute to hypercalcemia and hyperphosphatemia, both of which have been associated with increased morbidity and mortality in patients who receive dialysis (27).…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Other studies also have shown that IV route is associated with fewer episodes of hypercalcemia than the oral administered route. 17,18 IV alfacalcidol administration bypasses intestinal degradation of the hormone and thereby achieves a concentration of the active VD compound in the parathyroid glands where it causes a direct inhibition of PTH synthesis through action on the specific VD receptors before any significant rise in serum Ca or P. 19 In this study, IV alfacalcidol pulse therapy reduced i-PTH by 55 ± 25.43 pmol/L and 50.55 ± 20.79 pmol/ L after 6 months of therapy in Groups 1and 2, respectively, this representing a median reduction of 60% from baseline. The cumulative experience indicates that this is considered a successful response to alfacalcidol.…”
Section: Discussionmentioning
confidence: 99%